(untitled) (Journal of Civil Engineering Researchers, 2025)
Base isolation solutions are efficient alternatives for seismic protection of buildings and for enhancing resilient capacity. Currently, seismic isolation is focused principally on the critical infrastructure of public health, transportation, education, etc. The seismic response of multi storied base-isolated structure to various types of isolation systems connected using viscoelastic dampers to the adjacent dissimilar base isolated or fixed base structure is investigated. The multi- storied structures are modelled as a shear type structure with lateral degree of freedom at each floor, which are connected at different floor levels by viscoelastic dampers. The variation of top floor absolute acceleration of both the buildings and bearing displacement under different real earthquake ground motions is computed to study the behavior and effectiveness of resulting connected system. It is concluded that connecting the two adjacent base isolated buildings with the viscoelastic dampers is useful in controlling large hearing displacements in the base isolated structures thereby eliminating the isolator damages arising due to instar billet at these large displacements or pounding with adjacent ground structures during earthquakes. The viscoelastic damper connection between adjacent structures is found to be most effective when the adjacent base-isolated and fixed base buildings are competed. Such scheme is hence useful in upgrading the seismic performance of existing fixed base structures adjacent to a base isolated structure.